Crime Investigation in the Mahabharata Novel by Nyoman S. Pendit (Forensic Linguistic Study) - Fitrah, Yundi; Putra, Yoga Mestika; Putri, Aprilia Kartika; Fitriah, Siti (Proceeding International Conference on Malay Identity, 2023)
The criminal case in the novel "Mahabharata" leaves evidence of language, such as the utterance of sentences in the novel.  This research aims to find ways and forms of crime through a forensic linguistic approach. This type of research is descriptive qualitative. Using the novel " Mahabharata" by Nyoman S. Pendit as the primary data source, while the secondary data source uses published forensic linguistic articles. Data collection techniques in this study used reading and note-taking techniques. The language equivalent method is used to analyze the data. The threat utterances analyzed are based on Fraser's (1998) threat language indicators. In terms of form, this research uses the theories of Austin (1962) and Searle (1969). In terms of meaning, Löbner's (2013) theory is used, and in terms of motives, Maslow's (2017) theory is used. The results of the overall analysis of 10 data show that in terms of form, language is a threat in the novel Mahabharata Nyoman S. Pendit's work has locutionary, illocutionary, and perlocutionary forms. Abstrak Kasus kriminalitas dalam novel "Mahabharata" meninggalkan bukti-bukti bahasa, seperti pengucapan kalimat-kalimat dalam novel tersebut.  Penelitian ini bertujuan untuk menemukan cara dan bentuk kejahatan melalui pendekatan linguistik forensik. Jenis penelitian ini adalah deskriptif kualitatif. Menggunakan novel "Mahabharata" karya Nyoman S. Pendit sebagai sumber data primer, sedangkan sumber data sekunder menggunakan artikel-artikel linguistik forensik yang telah dipublikasikan. Teknik pengumpulan data dalam penelitian ini menggunakan teknik baca dan catat. Metode padan bahasa digunakan untuk menganalisis data. Tuturan ancaman yang dianalisis berdasarkan indikator bahasa ancaman dari Fraser (1998). Dari segi bentuk, penelitian ini menggunakan teori Austin (1962) dan Searle (1969). Dari segi makna, digunakan teori Löbner (2013), dan dari segi motif digunakan teori Maslow (2017). Hasil analisis keseluruhan dari 10 data menunjukkan bahwa dari segi bentuk, bahasa ancaman dalam novel Mahabharata karya Nyoman S. Pendit memiliki bentuk lokusi, ilokusi, dan perlokusi.